2018
DOI: 10.1002/adma.201706956
|View full text |Cite
|
Sign up to set email alerts
|

High‐Z Sensitized Plastic Scintillators: A Review

Abstract: The need for affordable and reliable radiation detectors has prompted significant investment in new radiation detector materials, due to concerns about national security and nuclear nonproliferation. Plastic scintillators provide an affordable approach to large volume detectors, yet their performance for high-energy gamma radiation is severely limited by the small radiation stopping power inherent to their low atomic number. Although some sensitization attempts with organometallics were made in the 1950s to 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
158
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(160 citation statements)
references
References 50 publications
2
158
0
Order By: Relevance
“…Luminescent NPs—metals, semiconductors, or insulators—have come to the forefront in modern solid state physics, lighting, next generation electronics, and sensing, in the environmental and life science, as well as in medical and biological fields . In particular, extensive theoretical and spectroscopic studies of the optical response of inorganic luminescent NPs have been proving the suitability of these systems in the field of phosphors and scintillators for lighting and radiation detection applications . For instance, defect‐engineering strategies can be applied in wide bandgap nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent NPs—metals, semiconductors, or insulators—have come to the forefront in modern solid state physics, lighting, next generation electronics, and sensing, in the environmental and life science, as well as in medical and biological fields . In particular, extensive theoretical and spectroscopic studies of the optical response of inorganic luminescent NPs have been proving the suitability of these systems in the field of phosphors and scintillators for lighting and radiation detection applications . For instance, defect‐engineering strategies can be applied in wide bandgap nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the samples embedding QD at the concentrations of 0.003 and 0.015 wt% show a light yield increase of 8% and 3% in comparison with the undoped PSS sample, respectively. As the optical contribution of the QDs to the total emission can be considered from Figure a–g as negligible, the increasing light yield is correlated with the high‐Z sensitization offered by the nanocrystals . In fact, for γ‐irradiation, it has been already demonstrated that the presence of inorganic nanocrystals within an organic polymer favors the conversion of γ‐photons into photoelectrons, although the excitation events subsequently occur within the organic material .…”
Section: Resultsmentioning
confidence: 93%
“…As the optical contribution of the QDs to the total emission can be considered from Figure 4a-g as negligible, the increasing light yield is correlated with the high-Z sensitization offered by the nanocrystals. [29] In fact, for γ-irradiation, it has been already demonstrated that the presence of inorganic nanocrystals within an organic polymer favors the conversion of γ-photons into photoelectrons, although the excitation events subsequently occur within the organic material. [29] Similarly, in our case, the presence of nanocrystals increases the specific energy loss experienced by protons, although the ionization and excitation events mainly occur within the polymer, giving rise to the enhanced luminescence in comparison with the pure PSS (Figure 5a).…”
Section: Proton-induced Luminescencementioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the low density of the chemical composition, organic scintillators still display several drawbacks in detecting high‐energy photons . Organic chromophores are precluded in this article, interested readers can find review articles from Hamel and Pei and co‐workers, in which the status of organic scintillators is comprehensively summarized . Metal ion‐based emitters are substantially utilized to build inorganic scintillators owing to their high energy conversion efficiency and energy resolution .…”
Section: Introductionmentioning
confidence: 99%